A novel hot pack rolling of high Nb–TiAl sheet from cast ingot. (December 2015) - Shen, Z.Z.; Lin, J.P.; Liang, Y.F.; Zhang, L.Q.; Shang, S.L.; Liu, Z.K.
Abstract: High-Nb containing (6–10 at.%) TiAl alloys exhibit excellent high-temperature strength and oxidation resistance. However, they are difficult to be fabricated into sheet in comparison with the conventional TiAl alloys. In the present work, the hot-deformation behavior of a high Nb–TiAl alloy (Ti–45Al-8.5Nb-0.2W-0.2B-0.03Y) was investigated. Hot-rolling process was optimized and carried out directly from the PAM (Plasma Arc Melting) ingot without the hot isostatic pressing (HIP) and hot forging. The hot-rolled sheets were successfully manufactured with dimensions up to 360 mm × 100 mm × 3.5 mm. The microstructure of as-rolled sheet is a typical "near gamma" characteristic with an average grain size about 15 μm. In the view of breakdown the lamellar colonies of high Nb–TiAl alloy ingot, the direct hot-rolling process has advantage over hot can forging and extrusion. Moreover, mechanical properties at room and high temperatures were also tested. Noteworthily, the as-rolled high Nb–TiAl alloy shows superplasticity above 950 °C at relatively high strain rate of 5 × 10 −4 . Highlights: The high Nb–TiAl sheet is directly fabricated from as-cast PAM ingot without the HIP and forging. The coarse lamella colonies of ingot can be completely broken by hot pack rolling and homogenous microstructure is obtained. There is weak cubic texture in the high Nb–TiAl sheet, which is caused by recrystallization. The sheet shows superplasticity above 950 °C at relatively high strain rate.